2018
DOI: 10.1111/jfs.12565
|View full text |Cite
|
Sign up to set email alerts
|

Screening of lactic acid bacteria isolated from fermented Cornus officinalis fruits for probiotic potential

Abstract: The objective of this study was to screen probiotic lactic acid bacteria (LAB) with beneficial properties such as acid and bile salt tolerance, antibacterial activity, autoaggregation ability, and cholesterol‐lowering capacity from fermented Cornus officinalis fruits. Eleven probiotic LAB strains, identified as ten Lactobacillus plantarum and one Lactobacillus casei, were screened out and evaluated by in vitro tests. The results of principal component analysis (PCA) based on probiotic characteristics suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
4
8
0
Order By: Relevance
“…This is as a result of their membrane impermeability. Similarly, high natural resistant to ciprofloxacin as obtained in our work has also been reported by Tang et al [57]. Jose et al [26] have previously reported tetracycline resistance from LAB strains isolated from milk, animal rumen and most commercial probiotics.…”
Section: Discussionsupporting
confidence: 89%
“…This is as a result of their membrane impermeability. Similarly, high natural resistant to ciprofloxacin as obtained in our work has also been reported by Tang et al [57]. Jose et al [26] have previously reported tetracycline resistance from LAB strains isolated from milk, animal rumen and most commercial probiotics.…”
Section: Discussionsupporting
confidence: 89%
“…As reported by Haghshenas et al [37], Lactobacillus strains isolated from Iranian fermented dairy products survived (71% to 76%) at pH 2.5 for 3 h. From the previous investigations, it has generally been accepted that an isolate with full tolerance to pH 3.0 for 3 h can be considered as high-acid-resistant strain with promising probiotic properties [36, 38]. Very recently, Tang et al [39] have reported that all the 9 Lactobacillus plantarum strains recovered from the faeces of breast-feeding piglets were found to be highly tolerant to pH 3 for 3 h.…”
Section: Discussionmentioning
confidence: 99%
“…These results concurred with the findings of Mathara et al (2008), who reported that LAB strains from milk were tolerant to bile salts at 0.1 to 0.5%. The ability of LAB from different sources to tolerate bile salt have been previously reported (Tang et al, 2018). During digestion, phenol, a toxic metabolite with bacteriostatic properties, is secreted in the GIT (Suskovic et al, 1997).…”
Section: Discussionmentioning
confidence: 99%